Methotrexate Effectively Controls Ocular Inflammation in Japanese Patients With Non-infectious Uveitis - Harada, Yosuke; Hiyama, Tomona; Kiuchi, Yoshiaki (Frontiers in Medicine, 2021)
This single-center retrospective study investigated the clinical characteristics and efficacy of methotrexate (MTX) for the treatment of non-infectious uveitis for more than 6 months at Hiroshima University, from February 2016 to May 2021. Outcome variables included changes in systemic immunosuppressive treatment and intraocular inflammation. Out of 448 patients with non-infectious uveitis, 35 patients (14 male patients and 21 female patients; 65 eyes) treated with MTX for more than 6 months were analyzed. There were 15 patients with anterior uveitis and 20 with posterior and panuveitis. The mean dose of systemic corticosteroids decreased from 12.1 mg/day at baseline to 1.3 mg/day at 6 months and 0.6 mg at 12 months after starting MTX, and approximately 90% of patients were corticosteroid-free at 12 months. The percentage of eyes with inactive uveitis at 6, 12, and 24 months was 49.2%, 59.6%, and 90.0%, respectively. Mean relapse rate score also significantly decreased from 2.88 at baseline to 0.85 at 12 months (p < 0.001). Inflammatory control was achieved with MTX doses of 8–16 mg/week, with a median dose of 12 mg/week. Adverse effects of MTX were observed in 34.3% of patients, and 11.4% required discontinuation; most commonly hepatotoxicity (58.3%), followed by fatigue (25.0%), and hair loss (16.7%). No significant differences were found between the survival curves of patients with anterior uveitis and posterior/panuveitis (Wilcoxon rank-sum test). The percentage of eyes without IOP-lowering eye drops was significantly higher in patients with posterior/panuveitis at 24 months (p = 0.001). Our study suggests that MTX is effective in controlling ocular inflammation for Japanese patients with non-infectious uveitis. Relatively high incidence of MTX-related adverse effects in the Japanese population indicates that careful monitoring and dose adjustments are crucial for the long-term use of this therapy.